2000
DOI: 10.1099/0022-1317-81-2-335
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Aleutian mink disease parvovirus in mink lymph node histocultures

Abstract: Aleutian mink disease parvovirus (ADV), causes an immune disorder with a persistent infection of lymphoid organs in adult mink. We studied replication of ADV in gel-supported histocultures prepared from adult mink mesenteric lymph node (MLN). Evidence of virus replication in the histocultures was first observed by indirect immunofluorescence 72 h after incubation with virus. Cells resembling lymphocytes and macrophages contained both ADV capsid (VP2) and nonstructural (NS1 and NS2) proteins, and were present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It has been recently found that RAB32 promotes the proliferation of effector CD8 + T cells in response to the challenges with cellular antigens in-vivo 64 . With regards to AD, cytotoxic T cells (CD8+) functions and their interferon signaling pathway play critical roles in the restriction of AMDV persistence and replication 65 , 66 . Another candidate gene is SERINC1 encoding Serine Incorporator 1, which facilitates the synthesis of serine-derived lipids 67 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently found that RAB32 promotes the proliferation of effector CD8 + T cells in response to the challenges with cellular antigens in-vivo 64 . With regards to AD, cytotoxic T cells (CD8+) functions and their interferon signaling pathway play critical roles in the restriction of AMDV persistence and replication 65 , 66 . Another candidate gene is SERINC1 encoding Serine Incorporator 1, which facilitates the synthesis of serine-derived lipids 67 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the viral-induced cell cycle arrest makes the infected cells poor targets for cytotoxic T lymphocytes (CTLs), which promotes the intracellular persistence of AMDV ( Oleksiewicz and Alexandersen, 1997 ). In this form of AD, the virus noncytopathicly replicates in lymphoid tissue, specifically macrophages and B cells; however, the replication of the virus is partially restricted with cytotoxic T cells ( Alexandersen et al., 1988 ; Jensen et al., 2000 ; Kanno et al., 1992 ). The humoral immune response plays a pivotal role in the pathogenesis of the virus in adults, as a severe polyclonal hypergammaglobulinemia or plasmacytosis, with -globulin constituting up to half of the total serum proteins, is the hallmark of the progressive form of AD ( Bloom et al., 1994 ).…”
Section: Amdv Replication Cycle Pathogenesis and Cell Tropismmentioning
confidence: 99%
“…Another explanation is the impaired down-regulation of the germinal center reaction by tingible body macrophages ( Fig. 4 c), resulting in unrestricted expansion of B cell populations and antibody production ( Jensen et al., 2000 ). The upregulation of cytokines of IL-4, mainly in CTLs, and IL-6 in infected macrophages stimulate differentiation of B cells into plasma cells, enhance antibody production, and facilitates virus replication ( Fig.…”
Section: Amdv Replication Cycle Pathogenesis and Cell Tropismmentioning
confidence: 99%